Infectious complications as predictors of adverse outcome in a patient with systemic lupus erythematosus (clinical case) - N. M. Nikitina; O. L. Aleksandrova; Ye. N. Skryabina; N. A. Magdeeva (SINAPS LLC, 2019)
Systemic lupus erythematosus is a systemic autoimmune disease. Over the past decades, great success has been achieved in its treatment. However, mortality in systemic lupus erythematosus is still high. An adverse outcome may occur because of kidney damage, damage of the nervous system, severe hematological disorders, etc. The factor of unfavorable prognosis is infectious complications.The article presents a prospective clinical observation of a faytal case of severe course of systemic lupus erythematosus. The patient was treated in the rheumatology department of the State Regional Clinical Hospital in Saratov from 2007 to 2014.The presence of high disease activity, multiple system disorders - polyarthritis, lupus nephritis, hepatitis, leukopenia, and recurrent necrotizing cutaneous vasculitis required the administration of high doses of immunosuppressive drugs.The progressive course of the disease, resistance to hormonal therapy, the rapid development of infectious complications made the prognosis for the patient's life extremely unfavorable. Persistent autoimmune leukopenia was the background condition for the development of complications. We used combined therapy - the oral administration of high doses of glucocorticoids together with intravenous injections (pulse therapy), broad-spectrum antibacterial drugs, intravenous immunoglobulin, drugs that improve tissue trophy and microcirculation. It was possible to decrease the disease activity, and also to restore the functional activity of the patient, to maintain low disease activity for 3 years, to prolong the life of a young patient by 8 years. The adverse combination of high activity of systemic lupus erythematosus with recurrent soft tissue infections caused difficulties for the therapy. Administration of adequate doses of cytostatic and biological agents were impossible due to leukopenia and secondary infection, which led to the death of the patient.